Loneliness or Solitude: Which Will We Experience? - Rokach, Ami; Boulazreg, Samir (Ruch Filozoficzny, 2024)
Loneliness, social isolation, aloneness, and solitude are frequently used interchangeably but are actually different. Loneliness is particularly salient now, due to the international restrictions on social activities imposed as a result of COVID-19, which brought loneliness into open discussion worldwide. The article highlights loneliness as a multidimensional construct and reviews its impact on cognitive, behavioral and affective functioning. In doing so, particular attention is given to loneliness as it manifests through the various life stages, as well as how personal predisposition and contextual factors may exacerbate it. in this article we also review solitude, and a clear distinction between loneliness and solitude is established. Finally, we conclude by addressing the global claims of loneliness during the pandemic and its implications. We offer a point of view which may assist in coping with it.